The Impact of Green Marketing Strategies on Employees Green Performance: An HRM Perspective - Mohammad Alzu’bi, Rama; Kontor, Enikő (Economica, 2024)
The rising concerns of the influence of human actions on the environment has resulted in a growing focus in the field of management science, particularly Human Resource Management (HRM). The right direction of going green must be directly linked with Environmental, Economic, and social performance Also, the field of Green Marketing has recently gained significant interest from researchers and practitioners in the realm of consumer behavior. Marketing and HR are fundamental departments in any organization, and their collaboration is essential for the success and resilience of a business, especially if the focus on sustainable development. This research aim to identify the impact of GM on employees’ green performance (GP). Also, to enhance research efforts, and improve the search process for other researchers seeking relevant paper and future research. The research problem has been formulated with the question: Can green marketing impact employees’ green performance by adapting, implementing, and promoting environmentally conscious behavior and corporate sustainability. This article provides a systematic Literature Review of existing research as a methodology. This research found that business can use GM strategies to impact the employees GP. Therefore, promoting and encouraging environmentally conscious practices in the workplace and incorporating a “sustainable culture” will help employees feel healthier, more motivated to finish their work, easily communicating their ideas about best green practices, and more satisfied with the company.